INTERACTIVE SPEAKING CLASS USING ANIMATED VIDEO - Umaroh, Liya; Hafidhoh, Nisa’ul; Sugiyanto, Sugiyanto (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
Teaching English has its own challenges, especially teaching collage students who lack enthusiasm in learning English Subject.  Short responses show that they have less attention and do not really interest on the material. Another reason are because English is not their mother tongue but an international language which is not commonly used in their daily conversations. Teaching students with a variety of backgrounds understanding in English will make lecturer have to struggle so that the material can be immediately understood. The various problems  arise during  teaching and learning process including the material itself, the way lecturers teaching in class, teaching methodology, lack of motivation, fear to speak English and  feeling bored with the textbook. To overcome the arising problems that appear in  teaching and learning process some inovation must be carried out considering the technological sophistication has been so rapid. Animated video  were chosen in teaching speaking subjects on the topic “job interview“. The implementation of the study was carried out by an experimental method involving 4 classes, 2 classes as an experimental class and 2 other classes as a control class. Implementation is conducted for one semester. The results obtained that 85% of students are very interested in the material presented, do not feel bored and monotonous, the class is more interactive because it does not seem awkwardly. The results of the tests  included the acquisition of vocabulary, grammar, fluency, and pronunciation. So it can be concluded that the class is more interactive and has improved after it has been applied using Animated Video.